FEATURES OF T-HELPER IMMUNE RESPONSE IN YOUNG CHILDREN WITH CONGENITAL CLEFT LIP AND PALATE IN ACUTE PNEUMONIA - Aliev, Ахмаджон; Kamalov, Зайнитдин; Akhrorkhonov, Рустамхон (International Journal of Scientific Pediatrics, 2025)
А significant proportion of children with repeated acute respiratory infections (ARI) and recurrent chronic diseases of the respiratory tract and ENT organs are carriers of co-infections. Objective: to study the synthesis of key cytokines Th-1/ Th-2/ Th-17 types of immune responses in children with congenital cleft lip and palate in acute pneumonia. Material and methods: the present study included 38 children with an established diagnosis of acute pneumonia (18 infants with CCLP and 20 children without CCLP formed the comparison group) and 16 practically healthy children formed the control group. The concentration of interleukins and interferon-gamma in the blood serum was determined by solid-phase enzyme immunoassay using test systems of Vector-Best JSC (Novosibirsk, Russia). Results: It was found that in the groups of children with pneumonia, both with cleft lip and palate and without congenital pathology, there was a significant increase in the content of IL-17A, IL-4 in the peripheral blood and a deficiency of IFN-γ in children of the first year of life, which indicates an imbalance in the immune response that can affect the course and severity of the infection. Conclusions: The study of the cytokine profile in a comparative aspect revealed hypersecretion of key mediators of the Th2 and Th17 immune response (IL-4 and IL-17A) and a deficiency in the synthesis of the key antiviral cytokine Th1 immune response (IFN γ) in all groups of children with pneumonia.